2017
DOI: 10.1111/add.13803
|View full text |Cite
|
Sign up to set email alerts
|

High risk of overdose death following release from prison: variations in mortality during a 15-year observation period

Abstract: There is an elevated risk of death from drug overdose among individuals released from Norwegian prisons, peaking in the first week. The risk has reduced since 2000-04, but is greatest for those serving 3-12 months compared with shorter or longer periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 29 publications
(47 reference statements)
3
68
0
4
Order By: Relevance
“…There is an established literature documenting an elevated risk of premature death in the first four weeks after release from incarceration [12][13][14][15][16]. However, the specificity of this increased risk window -and beyond -has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an established literature documenting an elevated risk of premature death in the first four weeks after release from incarceration [12][13][14][15][16]. However, the specificity of this increased risk window -and beyond -has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…However, their analyses were based on suicide deaths only and were restricted to the five studies (out of nine) with sufficient published data to be included in the meta-analysis. Merrall et al [12] conducted a meta-analysis of studies examining drug-related deaths follow-ing prison release and reported an acute elevation in drug-related deaths in the first two weeks post-release. However, their analyses (a) were restricted to a single cause of death; (b) included only six studies that published their findings in a way that permitted metaanalysis; (c) were restricted to two-week intervals up to 12 weeks post-release, due to power limitations; and (d) did not disaggregate findings by specific sub-populations, limiting the generalisability of the findings.…”
Section: Introductionmentioning
confidence: 99%
“…Overdødeligheten ved selvmord etter soning er derimot registrert blant annet knyttet til rus-, marginaliserings-og integreringsproblemer (bl.a. Kjelsberg og Laake, 2010;Bukten et al, 2017).…”
Section: Selvmord I Fengsel Er Riktignok Stedbundet …unclassified
“…Amongst the factors related to increased mortality after release from prison is abuse of heroin and other opiates [8][9][10][11][12][13] , alcohol abuse is another factor, along with treatment with antidepressants in prison or recidivism, while some other factors such as being married may act as a protective factor 8 . Although the main cause of death after release is from overdose, the potential causes are numerous 6 and include chronic organic pathologies (cancer or heart disease), infectious diseases (such as HIV) 14 , or acts of violence (suicide, homicide or accidents).…”
Section: Health Services and Fairnessmentioning
confidence: 99%